PENGARUH GUIDANCE COACHING TERHADAP KINERJA TUGAS YANG DIMEDIASI OLEH KINERJA ADAPTIF PADA KARYAWAN PT. PLN UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) BANDA ACEH - Eva Arvianti; Nashrillah Nashrillah (Departemen Manajemen, 2021)
This study aims to examine the effect of Guidance Cocahing to task performance with Task Adaptive as a mediator for employees of PLN UP3 Banda Aceh. The sample used in this study were 141 employees using purposive sampling technique. Then, this study used data collection equipment, namely a questionnaire (questionnaire). This study uses Hpath analysis as an analytical method to determine the effect of the variables involved in mediation testing in this study. Based on the results of the path analysis, it shows that guidance coaching partially has a positive and significant influence to task performance and adaptive performance of PT PLN UP3 Banda Aceh employees. Adaptive performance also partially has a positive and significant influence to task performance of PT PLN UP3 Banda Aceh employees, and guidance coaching to task performance are not mediated by adaptive performance of PT PLN UP3 Banda Aceh employees.